Geotechnical Study of The Impact of Groundwater Level For Slope Stability in Coal Mine - Jioni Santo Frans; Muhammad Hafizh Nurfalaq (Indonesian Mining Professionals Journal, 2019)
Rock mass has force equilibrium which can be disturbed due to changes in rock mass conditions, both by naturally as well as human activities. In response, rock masses could have instability to reach new equilibrium and trigger landslides. Unstable slopes will affect the safety, economic and social factors. Groundwater has its own problems in mining management. Pore water pressure can cause uplift force and reduce the strength of the rock mass forming slopes and affect the slope stability. The study area has groundwater level relatively close to surface and causes the slope to be in nearly saturated condition. This research aims to study of the effect of groundwater levels on the stability of coal mine slopes in the study area. The research method includes collecting primary data through field observations to collect related technical data and secondary data collection through literature studies. Slope stability analysis was carried out to obtain recommendations with a minimum Safety Factor of 1.30. The results showed the ground water level has an inverse relationship to Safety Factor value. The recommendation is  depressurisation using drain holes. The target of groundwater level reduction in the mine wall is RL+40 in the sidewall area and RL+65 in the highwall area. Another alternative is is by resloping the overall slope angle of the mine wall in the study area. The mine slope is recommended for layback with an overall slope angle of around 24 °.